Արիստակես Լաստիվերցու Պատմությունը որպես Վահագն Դավթյանի «Թոնդրակեցիներ» պոեմի սկզբնաղբյուր - Գրիգորյան, Սեյրան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В исторической поэме «Тондракийцы» Ваагн Давтян среди других источников использовал книгу «Повествование» армянского историка XI века Аристакеса Ластиверци. На основе жанровых форм летописи и плача создан образ историка Симавона, прообразом которого является Ластиверци. В поэме «Тондракийцы» есть также образ безымянного скитальца, который везде произносит лишь: «Горе мне». Этот образ Давтян тоже взял из книги Аристакеса Ластиверци. Но эти формы и образы Ваагн Давтян представляет самостоятельными художественными преобразованиями и переосмыслениями. In “The Tondrakians” historical poem, Vahagn Davtyan, among other sources, used “History” of the 11th century Armenian historian Aristakes of Lastiver. Based on the genre forms of the chronicle and lamentation, the character of the historian Simavon was created, the prototype of which is Aristakes of Lastiver. In «The Tondrakians», the character of a nameless wanderer also exists, who everywhere says only these words: «Woe is me.» Vahagn Davtyan took this character from the book of Aristakes of Lastiver, too; however, he presents these forms and characters as independent artistic transformations and reinterpretations.
Keywords: Բանասիրություն; Պատմություն